(3GdGSJbUG aj GdePgH TQM GdegPHs - (3VjGA GdOjf CHhYeQh YKeGf Hf YjSi Hf Ydj Hf OQjGS GdcQOj GdeGQGfjs; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s ((3YHOGdYXje Hf aJhM Hf YHOGddg s)
(3ChdgG (B:s
(3Ohf GdfaS cGdfaS aj GdMGLI Edi MaXI HGdbUGU s
(3BNQgG (B:s
(3aUd hEf VQH HWf CeJg hCYJbgG fLR GdLRA GdJGSY YTQ ef GdESJbUGA hHGddg GdJhajb s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1912s
Keywords: (3Gdabg GdTGaYjs